Gynecological acute abdomen in pregnant women. - Castellano, Carlos (2015)
This syndrome of varied etiology, is characterized by more or less intense and persistent abdominal pain, accompanied by a set of symptoms and signs that are usually caused by intra-abdominal processes; often, eventually, they will cause first located and then in many cases, acute generalized peritonitis. This peritoneal box, if left to evolve freely, take the patient to the toxic and hypovolemic shock, progressive and irreversible progress, and ultimately death.